Kierkegaard’s postmodern challenges for media - Tkachova, Hedviga (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2014)
Kierkegaard is one very few providential thinkers of the 19th century who paid attention to the changes with respect to humans, their conduct, habits, and their interaction in a society headed toward postmodernism. Already in the first half of the 19th century, Kierkegaard offered a prophetic vision reflecting our present society the mechanisms of which transform human individuals into a mass without any individual reflection. He thereby depicts the tendencies of the present mass society that is permeated by modern forms of information and their distribution. Kierkegaard, thus, confronts this ‘mass progress’ with the imperative of respecting human individuality, defending the human subject from uncritically receiving the various ideologies and benefits of the current society as they are presented by the media. The contribution analyzes Kierkegaard’s challenges to postmodern media – as shapers of public opinion and prevalent societal attributes